Three new species of Scythrididae from the northern Tien-Shan Mountains (Lepidoptera: Scythrididae) - Nupponen, Kari; Sinev, Sergey Yu. (Entomologica Fennica, 2011)
Three new species of the family Scythrididae are described from Central Asian mountains: Scythris cultelloides Nupponen & Sinev, sp. n., S. danilevskyi Nupponen & Sinev, sp. n. and S. ganesha Nupponen & Sinev, sp. n. One unknown species is reported but not formally described because only a single female is available.